EXCHANGE OF CARBON BETWEEN THE BOTTOM WATER AND THE BOTTOM SEDIMENTS IN THE SEA OF OKHOTSK - Bordovskiy O.K.; Semiletov I.P. (My University, 1989)
The principal sink in the circulation of carbon in the ocean is its settling as organic matter and carbonates. But about 40 percent of the organic matter is decomposed in the initial stage of sediment development. Due to a change in the carbonate equilibrium as a result of decomposition of the organic matter, some of the calcareous carbon goes into solution. Little is known about diffusive flow of the carbon circulation, resulting in an underevaluation of the role of the ocean as the reservoir and regulator of the CO2 concentration in the ocean-atmosphere system. During the 7th cruise of the R/V Akademik A. Nesmeyanov, the authors investigated the carbonates in bottom-sediment cores from the Sea of Okhotsk between Sakhalin and Kamchatka. Results show that this quantity of CO2 released from this sediments into the bottom water is of the same order of magnitude as the average flow of CO2 from the atmosphere. The intonal and marginal seas, and probably also the coastal zones of the oceans, are points of release of carbon dioxide into the atmosphere. There is another interesting fact: as in the case of river discharge, the carbonate equilibrium suggests that carbon released from the sediments of the Sea of Okhotsk into the bottom water and that it is primarily in the form of bicarbonate.